Parachute Jump, New York World's Fair 1939 (Grinnell Litho Co.)
This 250 foot tower provides the more daring thrill seeker at the amusement area with a safe means of experiences the sensation of a parachute jump from the height of a 25 story building. This structure is one of the highest buildings at the Fair.